Quantitative assessment of floodplain functionality using an index of integrity. (April 2020) - Karpack, Marissa N.; Morrison, Ryan R.; McManamay, Ryan A.
Graphical abstract: Highlights: Anthropogenic stressors to specific floodplain functions are identified. A method is developed to quantify reductions to floodplain integrity. A floodplain integrity metric is mapped for the state of Colorado. Abstract: Floodplain integrity can be defined as the ability of a floodplain to support essential geomorphic, hydrologic, and ecological functions that maintain biodiversity and ecosystem services. Humans alter floodplain functionality by changing the physical landscape of the floodplain or by altering river flow regimes and subsequent floodplain inundation dynamics. This research evaluates floodplain integrity by assessing the prevalence of anthropogenic modifications to hydrology and landscape. Specifically, the objectives of this research are to: 1) develop a methodology to assess floodplain integrity using geospatial datasets available for large spatial scales; and 2) use the methodology to evaluate spatial patterns of floodplain integrity in the state of Colorado. To accomplish these objectives, we evaluated the critical floodplain functions of attenuating floods, storing groundwater, regulating sediment, providing habitat, and regulating organics and solutes. At present, this work is the first to quantify the integrity of specific floodplain functions instead of measuring floodplain health solely by ecological integrity. We applied the index of floodplain integrity methodology in the state of Colorado to analyze the integrity of each of the five floodplain functions and the aggregated overall integrity. In Colorado, overall floodplain integrity decreased as stream order increased above third order streams. Floodplain integrity was also lower in floodplains that intersected urban areas than those that did not, which indicates the index of floodplain integrity captured the adverse relationship between development and floodplain health established in literature. By quantifying anthropogenic reductions to floodplain functionality at broad spatial scales, the index of floodplain integrity can help target restoration efforts towards the most affected functions and areas.